Analysis Of Information Pertaining To Economic Life In The “Jahangirnama” - Botir Urolovich Yuldashev (Frontline Social Sciences and History Journal, 2025)
This article examines the political and economic measures implemented by the Mughal Emperor Nuruddin Muhammad Jahangir upon his accession to the throne at the beginning of the 17th century. Drawing primarily from the Emperor's own autobiography, the "Jahangirnama" (Tuzuk-i-Jahangiri), the study analyzes the financial strategies used to consolidate power. Key findings reveal Jahangir’s efforts to stabilize the court by eliminating factionalism and securing loyalty through significant salary increases for officials (a minimum of 20%) and the specialized military corps, the Ahadiys (50%). The research details the redistribution of high-ranking mansabs (ranks), showing Jahangir's reliance on both loyal Mavarounnahr-origin allies and prominent Indian figures like the Rajputs. Crucially, the paper explores the Emperor's comprehensive monetary reforms, including the introduction of new gold coins (Muhr, Nur Shahi, Nur Sultani) struck in unique weights (tolas) and inscribed with distinct poetic and religious phrases. These findings illuminate the early economic policies and administrative changes that underpinned Jahangir's reign, confirming his systematic approach to establishing political authority and fiscal stability through administrative hierarchy and currency control.